Prevalência de Diabetes Mellitus tipo 2 e fatores associados em adultos e idosos do Centro de Referência e Atenção ao Idoso - Ferranti, Liégi Tajana (2017)
Diabetes mellitus is characterized as a serious public health problem with high global prevalence. Among the related factors, those linked to lifestyle are the main responsible for increasing this incidence in the world. This essay is composed by a scientific production, whose objective was to describe the prevalence of type 2 diabetes mellitus and the associated factors in adults and the elderly women of a Center of Reference and Attention to the Elderly in the city of Passo Fundo, in partnership with the group of Research EloCreati. This is a cross-sectional study, a study entitled "Longitudinal Study of the Center for Reference and Attention to the Elderly: Elo-Creati". The sample consisted of adults and elderly women over 49 years old, Data were collected from August 2014 to August 2015. A questionnaire was applied with demographic, economic variables, presence of self-reported diseases, general health conditions, and physical activity level of the evaluated individuals.Measurements of waist circumference, weight and height were measured in triplicate. As a variable outcome, the presence of self-reported type 2 diabetes mellitus was considered and the risk factors analyzed were(age, color, schooling, marital status, socioeconomic class, BMI, waist circumference, physical activity level, smoking, history Family). This study was approved by the Research Ethics Committee of the University of Passo Fundo according to opinion No. 741.214 in 2014. The sample consisted of 411 adults and elderly women, and the prevalence of diabetes was 13%. The majority of the evaluated ones had age between 60 and 79 years (77,4%), with predominantly white skin color (84,5%). With regard to schooling, 60.3% of the students presented 12 years or more of studies, the majority lived without the partner (58.2%) and economic classes B and C were the most prevalent classes (94%). The predominant body mass index was eutrophy (52.8%), waist circumference had high values (68.6%) and most of the people were sufficiently active or very active (58.2%). Most of the participants stated that they never smoked (73.2%) and 76.9% of the people did not have a family history. The presence of DM2 is associated with overweight, presence of family history, and lower educational level (p <0.05). The results can serve as food and nutrition program subsidies to improve the nutritional status of the researched population. This dissertation has identified the need for more research on the associated factors and ways of care in the population in order to guide and carry out prevention effectively.